Geological-environmental evaluation in determining the feasibility of an area for sanitary landfill - Allende Ccahuana, Teófilo (2001)
The landfill area is a physical space that has no environmental technical condition and high demand costs for project implementation , because the physical elements of nature are utilized. The feasibility of using landfill area is based on geological environmental assessment , which means fixing all environmental technical aspects : location, accessibility, topography , geology , climate, water surface and ground conditions, physical security aspects and conditions : air safety, integrity of natural resources and cultural assets , existing infrastructure , projects of urban, regional and national development, among others. The present work is a document containing the reasons for the use of a landfill , restrictions and criteria for the selection of an area. Also summarizes the lessons learned in the areas proposed for landfill for the municipalities that were assessed as feasible areas in the various departments of Peru like Arequipa , Apurimac , Huancavelica , Ayacucho , Cusco , Junín , Lima, Ancash , Lambayeque , La Libertad, San Martín , Loreto, Piura and Tumbes.